2021
DOI: 10.1002/nano.202100095
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites obtained by incorporation of silanized silver nanowires to improve mechanical properties and prevent fungal adhesion

Abstract: In this work, the surfaces of silver nanowires (AgNWs) were modified by silanization process to improve the mechanical and antibiofilm properties of polymethylmethacrylate (PMMA) dental resins. A two-route methodology was used to silanize the AgNWs: first, a surface treatment using tetraethyl orthosilicate (TEOS) was performed to act as interface agent; and then, γmethacryloxypropyltrimethoxysilane (MPS) was used to insert functional groups compatible to the acrylic resin. PMMA/AgNWs composites were obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Although the reduction was not statistically significant, there was a 64% reduction in the CFU/specimen count between CG and G1. In another study, a reduction of about 50% in the biofilm formation was observed for the nanocomposites with incorporation of silver nanowires [ 61 ]. Li et al [ 62 ] found that there was a biomass percentage reduction of C. albicans with the use of a AgNPs suspension on a denture base made of acrylic resin.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reduction was not statistically significant, there was a 64% reduction in the CFU/specimen count between CG and G1. In another study, a reduction of about 50% in the biofilm formation was observed for the nanocomposites with incorporation of silver nanowires [ 61 ]. Li et al [ 62 ] found that there was a biomass percentage reduction of C. albicans with the use of a AgNPs suspension on a denture base made of acrylic resin.…”
Section: Discussionmentioning
confidence: 99%
“…By combining the AgNWs conductive thin films with the substrate, a gate-shaped sensitive structure is generated. This approach aims to minimize the lateral effects experienced by the strain sensor [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%